Implementasi Kurikulum Pemrograman Komputer di Sekolah M.I. Jami’atul Khair Ciledug Tangerang - Prasvita, Desta Sandya; Santoni, Mayanda Mega; Muliawati, Anita (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2024)
Community service activities are carried out at Madrasah Ibtidaiyah (M.I.) Jamiatul Khair is one of the private elementary schools in the Ciledug District, Tangerang City. This activity has been going on for three years. In 2020, teachers were given material related to using Google Classroom to support distance learning (PJJ) activities at the start of the pandemic. In 2021, community service activities will be carried out with the theme of making learning videos. Apart from that, in the same year, teachers also received learning related to using office applications. Through evaluation of previous activities, we assess that teachers have acquired the ability to use advanced computers to support the learning process. Therefore, in 2022, community service activities will be carried out to implement the school programming curriculum. Teachers teach computational thinking with the intention of integrating these concepts into student learning. Computational logic thinking, involving concepts such as sequential logic, branching, and looping, is applied interestingly so that it is easy to implement for M.I. students. Jamiatul Khair. During this activity, the teachers showed high enthusiasm for the training process. Activities were carried out smoothly without experiencing significant obstacles. The evaluation results also reflect positive feedback and a high level of satisfaction regarding the material presented and the assessment of the resource persons.